INSTITUTIONAL AND FINANCIAL CONDITIONS FOR THE DEVELOPMENT OF RURAL TOURISM IN THE REPUBLIC OF SERBIA: A CASE STUDY - Mihailović, Branko Miodrag; Radosavljević, Katica; Paraušić, Vesna; Pantović, Danijela (Economics of Agriculture, 2025)
This paper explores the institutional and financial conditions that determine the development of rural tourism in the Republic of Serbia, as well as the challenges faced by entrepreneurs in rural areas. Through a systematic examination of relevant institutional policies and financial mechanisms, the study aims to identify key factors that foster development and influence the sustainability of rural tourism. Additionally, by conducting interviews with the owners of five rural tourism households in Serbia as representative stakeholders, the authors analyzed specific circumstances and challenges in rural tourism, providing valuable insights into the practical aspects of institutional and financial regulation in this sector. This analysis offers policy recommendations for improving institutional and financial conditions for rural tourism, and provides guidelines for potential investors. Furthermore, the research aims to contribute to the promotion of entrepreneurship in rural areas, the further development of rural tourism in Serbia, and, consequently, the strengthening of rural sustainability.